Strategic Financial Planning of Ev-Station Voltwave Network: A Case Study From Indonesia's Ev Infrastructure Sector - Fathoni, Rialdi Fuad; Indradewa, Rhian; Iskandar, Muhammad Dhafi; Negoro, Dimas Angga (Syntax Corporation, 2025)
This article explores the strategic financial planning of eV-Station Voltwave Network, a startup focused on developing Electric Vehicle Charging Station (SPKLU) infrastructure in Indonesia. The financial model is built upon five core pillars: financial objectives, planning elements, revenue projection, investment feasibility and financial performance analysis. Over a five-year horizon, total projected revenue reaches approximately IDR 48.49 billion, sourced from ultra- fast charging services, event space rentals, robotic carwash operations and tenant leasing for commercial zones such as food courts and ATM galleries. Cost planning covers marketing, operations, human resources and risk management incorporating a straight-line depreciation model to stabilize financial reporting. The company’s targets include a minimum Return on Investment (ROI) of 10% annually and a cost-to-income ratio below 60%. The financial viability is affirmed by positive Net Present Value (NPV) an Internal Rate of Return (IRR) exceeding the borrowing rate, and a payback period of 4.8 years. Risk mitigation strategies are aligned with the ISO 31000 framework, ensuring operational and financial resilience. This financial planning approach offers a scalable and sustainable model for emerging startups in Indonesia’s electric mobility ecosystem.